The Automobile and the Regulation of Some of Its Non-Exhaust Impacts on the Environment - Grad, Frank P.; Rosenthal, Albert J.; Hsia, Richard; Munzer, Stephen R.; Schwarcz, Stephen L. (Columbia Journal of Environmental Law, 2019)
The automobile lies at the heart of one of our country’s most pro- found environmental and economic dilemmas. The mass availability of automotive transportation has become an integral part of the American life style, and the production, distribution and servicing of automobiles and the related fuel industry have become major elements of the American economy. In addition, a vast number of other industries and commercial interests (such as, notably, high- way building and the recreation industry), as well as many urban concerns are related to the automobile. While the automobile is a mainstay of the American economy, a whole set of side effects- from the contribution to deterioration of air quality in urban areas, to urban congestion and urban noise-have made the automobile one of the principle foci of environmental, and most recently, energy, concerns. It was to describe and analyze these side-effects, as well as to examine current and possible future means of minimizing environ- mental hazards, that a study was begun in September 1971-funded by the National Science Foundation (RANN-Research Addressed to National Needs), and sponsored by the Special Committee on Science and Law of the Association of the Bar of the City of New York, which also acted as advisory committee to the project. The results of that study have recently been published by the Legislative Drafting Research Fund under the title The Automobile and the Regulation of Its Impact on the EnvironmentJt The main emphasis of the study-as in most recent studies that focus on the automobile-was on problems of the regulation of automotive air pollution. The chapters here reproduced-Chapters 10, 11, and 12- however, deal with other aspects of the environmental impact of the automobile-in the areas of noise, water pollution and solid waste- that should receive greater attention than they have in the past. The investigators primarily responsible for the work are Professors Frank P. Grad and Albert J. Rosenthal, of Columbia Law School, who acted as co-directors of the study at the Legislative Drafting Research Fund, and Laurie R. Rockett, associate director; Professors James A. Fay and John Heywood, at the Massachusetts Institute of Technology, who assumed responsibility for the technical automo- tive portion of the study; and Professors John F. Kain, Gregory Ingram, and David Harrison at the Harvard University Department of Economics, and Thomas Tietenberg at Williams College, who were responsible for the economic analysis.